Aquaponic system development as an educational tourism destination in Sukowilangun Village, Malang Regency - Sufiyanto Sufiyanto; Mochammad Musafaul Anam; Zaid Dzulkarnain Zubizaretta (University of Merdeka Malang, 2021)
The tourism sector has been targeted to be a tool that may develop people’s economies. Kelompok Sadar Wisata (Pokdarwis) Sukowilangun Berseri is a community that develops Taman Suko at Sukowilangun, Kalipare, Malang Regency. However, the increasing number of tourism effects for the local community at Sukowilangun can still be categorized at a low level. Besides, the management capabilities and resources of the local community in developing Taman Suko as a local tourist destination have not been able to attract more tourists. We carry out a community service program through diversifying our business with the implementation of an aquaponics system to increase income derived from tourism management, providing assistance in efforts to develop tourism potential, and empowering local community-based communities at Taman Suko. The results of this program were implementing an aquaponics system as a business diversification as well as an education theme for tourists on how freshwater fish and vegetables are bred, developing some tourism support facilities such as photo spot, pathways, and fish pond, and promoting local culinary business through social media and a video profile.